LASER MELTED STEEL FREE SURFACE FORMATION (Metallurgy and Foundry Engineering, 2007)
Two-dimensional mathematical model of recasting steel by laser was presented in this paper. Surface velocity and liquid temperature for several powers of laser beams and sulfur contents were obtained as results of numerical modeling of liquid flow and heat exchange processes. The shape of free surface in a melted zone was computed with the use of iterative method proposed in this paper.